Wittgenstein e Bourdieu: diálogos para uma sociologia prática - Oliveira, Flaubert Mesquita de (2007)
The dialogue between philosopher Ludwig Wittgenstein s notions and Pierre Bourdieu s sociological concepts related to social practice of language shows that the philosophy of language has an important influence on contemporary social theory. When we compare the ideas of these authors we discover that beyond the direct influences from the philosopher that the sociologist recognizes there are great parallelisms of thought. That is, Wittgenstein s pragmatic thought of the use of language does not concern only language, but also every socially built behavior. When we notice that the social and linguistic behavior are borne by the individual in a tacit way, that leads us to theorize about the prereflective dimension that builds human actions and even the habits of thought. The same processes allow the uses of language to build wider social practices. Besides, John Austin, one of Wittgenstein s disciples, and his speech acts theory, contribute with a way to reflecting on how language ressembles a concrete action. Finally, the linguistc therapy that Wittgenstein means to be his philosophical proposal is assimilated by Bourdieu, who takes it as one of the necessary topics of the sociological work